Genetski vzroki spremenjene zgradbe migetalk pri človeku - Jezernik, Kristijan (Medicinski razgledi, 2001)
Amongst the recently well known groups of human disorders is the ciliary motility syndrome. It is caused by genetically-determinated defects of cilia, consequently leading to impaired transport of mucus and inhaled particles fromthe nasal cavity and the lung. The dysfunction of mucociliary clearance leads to recurrent respiratory infection and to chronic obstructive pulmonary disease. Many different proteins are involved in the structure of cilia therefore primary ciliary dyskinesia is a group of heterogenous disorders of yet exactly unknown origin. Despite of it electron microscopy is in strict correlation to cilia ultrastructure and with the beating pattern. The following article is an overview of the recent knowledge in the field of cell biology and genetics.
Keywords: Ciliary motility disorders; fiziologija; Genetics; migetalke; Cilia; genetske okvare; Ultrastructure; Pathology; Kartagener's syndrome